People Who Care, Share - Mayya Shmidt (Journal of Economic Sociology, 2017)
Thomas Widlok is Professor for African Studies and Chair for the Cultural Anthropology of Africa at the University of Cologne, Germany. In his latest book, Anthropology and the Economy of Sharing, Widlok addresses the rich pool of ethnographical material from hunter-gather societies to corporate shareholding to return sharing to anthropological analysis. The book is novel in its theoretical stance because it depicts the contemporary state of the anthropological agenda compared to mainstream economic anthropology. Widlok departs from the assumption that sharing is muchmore than a gift exchange theory and thus aims to theorize sharing in a unique manner. Thus, sharing is theorized as taking advantage of what is valued and taking opportunities for letting go. The major insights of the book are based on theoretical premises of the gift exchange theory. By rephrasing the well-known Mauss schema, Widlok suggests that “sharing creates and maintains social bonds through the opportunity to request, the opportunity to respond and the opportunity to renounce” (p. 79).